RAD51 as an immunohistochemistry-based marker of poly(ADP-ribose) polymerase inhibitor resistance in ovarian cancer - Kim, Yoo-Na; Kim, Kyeongmin; Joung, Je-Gun; Kim, Sang Wun; Kim, Sunghoon; Lee, Jung-Yun; Park, Eunhyang (Frontiers in Oncology, 2024)
Objective: Effective functional biomarkers that can be readily used in clinical practice to predict poly(ADP-ribose) polymerase inhibitor (PARPi) sensitivity are lacking. With the widespread adoption of PARPi maintenance therapy in ovarian cancer, particularly in patients with BRCA mutation or HR deficiencies, accurately identifying de novo or acquired resistance to PARPi has become critical in clinical practice. We investigated RAD51 immunohistochemistry (IHC) as a functional biomarker for predicting PARPi sensitivity in ovarian cancer. Methods: Ovarian cancer patients who had received PARPi and had archival tissue samples prior to PARPi exposure (“pre-PARPi”) and/or after progression on PARPi (“post-PARPi”) were selected. RAD51 IHC expression was semi-quantitatively evaluated using the H-score in geminin (a G2/S phase marker)- and γH2AX (a DNA damage marker)-positive tissues. A RAD51 H-score of 20 was used as the cutoff value. Results: In total, 72 samples from 56 patients were analyzed. The median RAD51 H-score was 20 (range: 0–90) overall, 10 (0–190) in pre-PARPi samples (n = 34), and 25 (1–170) in post-PARPi samples (n = 19). Among patients with BRCA mutations, RAD51-low patients had better progression-free survival (PFS) after PARPi treatment than RAD51-high patients (P = 0.029). No difference was found in PFS with respect to the genomic scar score (P = 0.930). Analysis of matched pre- and post-PARPi samples collected from 15 patients indicated an increase in the RAD51 H-score upon progression on PARPi, particularly among pre-PARPi low-RAD51-expressing patients. Conclusion: RAD51 is a potential functional IHC biomarker of de novo and acquired PARPi resistance in BRCA-mutated ovarian cancer and can be used to fine-tune ovarian cancer treatment.